Bead Weaving and Embroidery with Miyuki Beads : Instructions for Brick Stitch, Peyote Stitch, Square Stitch, and Loom Work; 100 Weaving Patterns /: Instructions for Brick Stitch, Peyote Stitch, Square Stitch, and Loom Work; 100 Weaving Patterns. (2022) - Chatenet, Virginie
No abstract available